Undermining the Everyday: Daphne Du Maurier’s Gothic Horror - Gina Wisker (Revue LISA)
Daphne Du Maurier’s Gothic horror destabilises the ordinary, the familiar everyday, revealing seemingly safe relationship and places to be undependable, even dangerous. Simultaneously, she disturbs the complacencies of familiar worldviews and the narratives with which we direct and understand our lives, including those of family, security, identity, order and romance. In Rebecca, “Ganymede”, “East Wind” and “The Birds”, she builds on Freud’s theory of the uncanny and the questioning of constructed reality offered by existentialism to undermine securities, upset self-deceptive internal narratives, inverting the familiar and unfamiliar in liminal places and spaces whether a grand house, exposed coast or a touristic version of Venice. Everyday anxieties flower into destructive realities as loved ones, idealised or homely places and creatures are no longer trustworthy and dependable, and indeed, it is revealed, they never were. As instability and the unknowable disturb complacencies and certainties in these narratives, Du Maurier overwrites the Gothic romance of popular fiction, replacing it with Gothic horror.